Research on the Development of Undergraduate Vocational Education - Taking Guizhou Vocational Education as an Example - Li, Yanyan; Zhang, Jiayong (Journal of Roi Kaensarn Academi, 2023)
In terms of law. From an international perspective, developed countries and regions with more successful development of undergraduate level vocational education have a relatively perfect legal system to guarantee it. On the contrary, the status of undergraduate vocational education in the higher education system, the equal legal status of applied technology universities and ordinary undergraduate institutions, and the right to confer undergraduate degrees in specialized vocational colleges have not been clarified. Both higher education legislation and vocational education legislation in China are sub-laws under education law, and the objects of legislation are school education institutions, which is a vertically structured legal system, and there is no legal regulation for different forms of educational institutions and school subjects at the meso level.